Impact of diabetes mellitus on urinary continence after holmium laser enucleation of the prostate due to lower urinary tract symptoms: a retrospective study - Acikgoz, Onur; Yilmaz, Mehmet; Aybal, Halil Cagri; Yilmaz, Sercan; Gazer, Eymen; Yalcin, Serdar; Duvarci, Mehmet; Kaya, Engin; Miernik, Arkadiusz; Tunc, Lutfi (POLISH UROLOGICAL ASSOC, 2021)
Introduction Diabetes mellitus (DM) is known as a risk factor of stress urinary incontinence after Holmium laser enucleation of the prostate (HoLEP). We aimed to compare the postoperative continence status of patients with and without DM, after HoLEP surgery. Material and methods A total of 214 patients who underwent HoLEP between January 2017 and January 2020 were retrospectively assessed. Functional outcomes, perioperative total operation time (TOT) (min), enucleation time (ET)(min), enucleation efficiency (EE)(g/min), enucleated tissue weight (ETW)(g), morcellation efficiency (ME)(g/min), morcellation time (MT)(min), continence status, intraoperative and postoperative complications according to Clavien-Dindo classification were recorded. Results A total of 96 patients had DM additional to benign prostate hyperplasia (BPH) (Group 1), while 118 patients had only benign prostate hyperplasia without DM (Group 2). When comparing preoperative and postoperative functional outcomes, a statistically significant improvement was observed in both groups from baseline to the 1st and 6th month follow-up (p <= 0.001). There were no statistically significant differences between groups in postoperative stress urinary incontinence at postoperative months 1 and 6 (1.7\% vs 2.1\%, p = 1 and 0.8\% vs 1\%, p = 1

respectively). There was no significant difference between groups in intraoperative and postoperative complications (p >0.05). Conclusions HoLEP is safe to perform in patients with DM at low complication and urinary incontinence rates.
Keywords: benign prostate hyperplasia; diabetes mellitus; enucleation; holmium laser enucleation of the prostate; stress urinary incontinence